Analisis Performansi Dan Simulasi ZRP (Zone Routing Protocol) Pada VANET (Vehicular Ad Hoc Network) Di Pekanbaru Pada Topology Hybrid Dengan Menggunakan Network Simulator 2 (NS-2) - Andika Prinanda; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of communication technology between vehicles has grown rapidly in recent years, where vehicle communications consists of vehicle and vehicle to infrastructure. Communication between vehicles uses wireless as the main component for communication thus making it easy for users to get various kinds of information including traffic light information, safety and comfort in driving. Based on Riau police traffic directorate, the number of vehicles in Pekanbaru in 2016 amounted to 83.270 vehicles, with a high population of vehicles causing the risk of accident and congestion in driving was also high. So that communication technology between vehicles is needed, better known as the vehicular ad hoc network, VANET is a wireless communication network that forms an ad hoc network, vehicles that are in the VANET network are called nodes. Nodes contained in VANET move freely and can communicate via wireless. In this scientific paper discuss the topic of performance and simulation of ZRP (zone routing protocol) on VANET in Pekanbaru on hybrid topology using network simulator 2 (NS-2). The method used in this scientific paper changes the number of nodes on the ZRP protocol using the SUMO and NS-2 applications, to see the Packet Delivery Ratio (PDR) performance metrics, End to End Delay and Routing Overhead. The simulation of the ZRP protocol performance analysis results obtained on each parameter are PDR 99.89 %, End to End Delay 0.1308 ms, Routing Overhead 42642 packet.Keywords : ZRP, VANET, Wireless, Topology Hybrid, Pekanbaru